public university - Armoh, Ebenezer Kingsley; Aboagye, Emmanuel (Ghana Journal of Higher Education Management, 2023)
Going to work just to be ineffective is a decade canker in our workplaces and it is very difficult to measure, especially in a typical Ghanaian community. This situation needs to be tackled as a matter of urgency. Being at the workplace and failing to function due to illness or stress can be very devastating for an institution or a company. The purpose of this paper is to draw University managers’ attention to an enemy of production in our workplaces which has been tagged ‘bureaucracy’. The researcher looked at what happens at the workplace every day, look at what the existing literature says about the phenomenon, and came out with the challenges and suggestions for possible eradication. The researcher believes that having a second look at the institution’s Welfare program to make sure administrative staff’s wellness is considered by making physical exercise a key to unlocking workers’ health will be a step in the right direction in reducing workplace presenteeism